Implementasi Program Pengajaran Sekolah Minggu Kreatif di GKSI Imanuel Teretek sebagai Bentuk Pengabdian Masyarakat untuk Meningkatkan Antusias Anak dalam Mengikuti Sekolah Minggu - Zagoto, Alfin Susanto (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2025)
The creative Sunday School teaching program at GKSI Imanuel Teretek was implemented as a community service initiative focused on increasing children’s enthusiasm for participating in spiritual activities. The program was motivated by initial findings showing that many children exhibited declining interest due to monotonous learning methods that lacked creative engagement. Therefore, the service team designed a series of activities based on creative approaches, including the use of visual media, educational games, art activities, and interactive storytelling to align learning with the developmental needs of children. The implementation process was carried out through several stages, including observation, material planning, activity execution, and evaluation. The results showed a significant increase in attendance, active participation, and positive responses from the children. They appeared more engaged, more willing to ask questions, and better able to remember biblical messages through enjoyable and easy-to-understand activities. Additionally, Sunday School teachers gained new insights regarding creative teaching strategies that can be applied sustainably. These findings affirm that innovation in teaching methods has a real impact on children’s learning motivation and strengthens the church’s role in nurturing faith from an early age.